Character education in the 21st century - Balraj Singh (Journal of Social Studies (JSS), 2019)
Character education is a growing discipline in recent times with the intent of optimizing student’s ethical behaviour. The outcome of character education has been seen in the continuous encouragement and preparation of a solid background of the leaders of tomorrow. The promotion of character education should not just be that of   lip service but should be followed-up with a concrete action plan that will stand the test of time. In other words, education policy should take the lead to actualize moral education. The stakeholders, including parent and Administrators should join hands and work together in making sure that the student’s exhibit good conduct and character in all aspects of their lives.  The outline of this paper was to identify and define the place of character education in our education system reviewing of the Character Education Partnership’s (hereafter CEP) eleven (11) principles of character education in the future, The Classroom/Activity-Based Character Education Program Implementation and finally the Models of Character Education: Perspectives and Developmental Issues, teaching Strategies and benefits of character education were also discussed.Keywords: character education, 21st century, teaching